CD93 is a cell surface lectin receptor involved in the control of the inflammatory response stimulated by exogenous DNA. Issue 2 (23rd July 2019) - Nativel, Brice; Ramin‐Mangata, Stéphane; Mevizou, Rudy; Figuester, Audrey; Andries, Jessica; Iwema, Thomas; Ikewaki, Nobunao; Gasque, Philippe; Viranaïcken, Wildriss
Summary: Bacterial DNA contains CpG oligonucleotide (ODN) motifs to trigger innate immune responses through the endosomal receptor Toll‐like receptor 9 (TLR9). One of the cell surface receptors to capture and deliver microbial DNA to intracellular TLR9 is the C‐type lectin molecule DEC‐205 through its N‐terminal C‐type lectin‐like domain (CTLD). CD93 is a cell surface protein and member of the lectin group XIV with a CTLD. We hypothesized that CD93 could interact with CpG motifs, and possibly serve as a novel receptor to deliver bacterial DNA to endosomal TLR9. Using ELISA and tryptophan fluorescence binding studies we observed that the soluble histidine‐tagged CD93‐CTLD was specifically binding to CpG ODN and bacterial DNA. Moreover, we found that CpG ODN could bind to CD93‐expressing IMR32 neuroblastoma cells and induced more robust interleukin‐6 secretion when compared with mock‐transfected IMR32 control cells. Our data argue for a possible contribution of CD93 to control cell responsiveness to bacterial DNA in a manner reminiscent of DEC‐205. We postulate that CD93 may act as a receptor at plasma membrane for DNA or CpG ODN and to grant delivery to endosomal TLR9. Abstract : The recognition of exogenous DNA leads to an inflammatory response. The exogenous DNA bind to CD93 and it deliver to endosomal TLR9. This process allows the production of proinflammatory cytokines mainly mediated by NF‐κB/AP1 pathway.